Clinical efficacy of irinotecan plus raltitrexed chemotherapy in refractory esophageal squamous cell cancer. Issue 4 (April 2020) - Liu, Min; Jia, Qingqing; Wang, Xiaolin; Sun, Changjiang; Yang, Jianqi; Chen, Yanliang; Li, Ying; Min, Lingfeng; Zhang, Xizhi; Zhu, Caiyun; Gubat, Johannes Artiaga; Chen, Yong
Abstract : Our retrospective study assessed the efficacy and safety of irinotecan plus raltitrexed in esophageal squamous cell cancer (ESCC) patients who were previously treated with multiple systemic therapies. Between January 2016 and December 2018, records of 38 ESCC patients who underwent irinotecan plus raltitrexed chemotherapy after at least one line of chemotherapy were reviewed. Efficacy assessment was performed every two cycles according to the RECIST version 1.1. A total of 95 cycles of chemotherapy were administered, and the median course was 3 (range 2–6). There was no treatment-related death. Nine patients had partial response, 21 had stable disease and eight had progressive disease. The overall objective response rate was 23.68% (9/38) and the disease control rate was78.94% (30/38). After a median follow-up of 18.5 months, the median progression-free survival and overall survival were 105 and 221 days, respectively. There were five patients (13.15%) with grade 3/4 leukopenia, three patients (7.89%) with grade 3/4 neutropenia and one patient (2.63%) with grade 3/4 diarrhea. The combination of irinotecan plus raltitrexed was effective for pretreated ESCC patients. Further studies are needed to determine the optimal dose of the two drugs.